ENVIRONMENTAL PESTICIDE RESIDUES AND HEALTH BIOMARKERS AMONG FARMERS FROM GREENHOUSES OF ERBIL CUCUMBER CROPS - & Kakey, Othman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to determine the residual concentrations of pesticides used in greenhouse cucumber fields and their effects on the farmers that spray it. Sixteen active cucumber greenhouse fields with 96 people (75 sprayers and 21 volunteers as control) randomly had been selected. In all selected greenhouses, abamectin, thiamethoxam, pyridabin, and spirodiclofen pesticides were used, their cucumber with leaves and groundwater collected in December 2017, March, June, and September 2018 with workers blood samples, were immediately brought to the laboratory. Results showed the occurrence of residual pesticides in the plant and groundwater samples with a highest level in the plant samples, while decreased in water samples. That is in comparison with control, sprayer blood results showed that cholinesterase activity decreased significantly meanwhile, liver function enzymes: serum glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, alkaline phosphatase, direct and total serum bilirubin increased significantly. The kidney function test revealed that the mean serum urea concentration in the sprayers was considerably increased compared to the controls, while there was no significant change between the sprayers and the control serum creatinine. Slight variations in the declining number of red blood cells; however, white blood cells have significantly risen to their upper limit within normal ranges.